Dual modification of predator and prey cell shapes during predation by Bdellovibrio bacteriovorus - Banks, Emma Jane (2022)
Bdellovibrio bacteriovorus HD100 is a vibrioid-shaped Gram-negative bacterium with an unusual predatory lifestyle. B. bacteriovorus attaches to, invades, and then replicates within Gram-negative prey bacteria including multi-drug resistant bacterial pathogens. Due to an extensive range of Gram-negative prey targets which are also incapable of developing genetic resistance to the invading predator, B. bacteriovorus presents itself as a potential novel antibacterial therapeutic within the worsening global antibiotic resistance crisis.